Direct Whole-Genome Sequencing of Sputum Accurately Identifies Drug-Resistant Mycobacterium tuberculosis Faster than MGIT Culture Sequencing - Doyle, Ronan M.; Burgess, Carrie; Williams, Rachel; Gorton, Rebecca; Booth, Helen; Brown, James; Bryant, Josephine M.; Chan, Jackie; Creer, Dean; Holdstock, Jolyon; Kunst, Heinke; Lozewicz, Stefan; et al. (Journal of clinical microbiology, 2018)
The current methods available to diagnose antimicrobial-resistant Mycobacterium tuberculosis infections require a positive culture or only test a limited number of resistance-associated mutations. A rapid accurate identification of antimicrobial resistance enables the prompt initiation of effective treatment. The current methods available to diagnose antimicrobial-resistant Mycobacterium tuberculosis infections require a positive culture or only test a limited number of resistance-associated mutations. A rapid accurate identification of antimicrobial resistance enables the prompt initiation of effective treatment. Here, we determine the utility of whole-genome sequencing (WGS) of M. tuberculosis directly from routinely obtained diagnostic sputum samples to provide a comprehensive resistance profile compared to that from mycobacterial growth indicator tube (MGIT) WGS. We sequenced M. tuberculosis from 43 sputum samples by targeted DNA enrichment using the Agilent SureSelectXT kit, and 43 MGIT positive samples from each participant. Thirty two (74%) sputum samples and 43 (100%) MGIT samples generated whole genomes. The times to antimicrobial resistance profiles and concordance were compared with Xpert MTB/RIF and phenotypic resistance testing from cultures of the same samples. Antibiotic susceptibility could be predicted from WGS of sputum within 5 days of sample receipt and up to 24 days earlier than WGS from MGIT culture and up to 31 days earlier than phenotypic testing. Direct sputum results could be reduced to 3 days with faster hybridization and if only regions encoding drug resistance are sequenced. We show that direct sputum sequencing has the potential to provide comprehensive resistance detection significantly faster than MGIT whole-genome sequencing or phenotypic testing of resistance from cultures in a clinical setting. This improved turnaround time enables prompt appropriate treatment with associated patient and health service benefits. Improvements in sample preparation are necessary to ensure comparable sensitivities and complete resistance profile predictions in all cases.